Residence site selection in urban and rural areas in Greece: a multiple-criteria decision analysis approach. (1st January 2012) - Thanos, Georgios A.; Vrachopoulos, Michalis Gr.; Koukou, Maria K.; Kakouris, Andreas P.; Koulis, Alexandros; Thanos, Athanasios
This research work focuses on the definition of the factors that determine the selection of residence site in urban and rural areas in Greece. The followed approach is based on an analysis that takes into account the nature and the peculiarities of the problem studied and it is built around a multiple-criteria methodology with reference to objective and subjective criteria, which constitute the quantitative and qualitative parameters of the system, respectively. The evaluation of the importance of each parameter separately, of each group of criteria and the total number of criteria (objective and subjective) for each area is attempted to define the final result (preference measure or priority) for the selection of residence site in urban and rural environments in Greece. Research findings provide indications that can lead to important conclusions and contribute to the development of policy proposals not only in Greece but also at international level with regard to the issues of: selection of location and residence, regional development, decentralisation as well as the study of the non-homogeneous and in-balanced development of urban and rural areas.